Impact on Neonatal Outcomes with Late Preterm and Early Term Delivery in Women with Diabetes - Austin, Brittany A.; McFarling, Kelli M.; Likins, Benjamin; Chapman, Alison; Cuff, Ryan D.; Head, Barbara; Finneran, Matthew M. (American Journal of Perinatology, 2023)
Objective Late preterm and early term deliveries are common in pregnancies complicated by diabetes due to higher rates of obstetric complications including increased stillbirth risk. However, early delivery is associated with multiple neonatal adverse outcomes, which may be further increased by maternal diabetes. We examined whether there is an additive effect on adverse neonatal outcomes in the setting of maternal diabetes in the late preterm and early term periods.Study Design This was a retrospective cohort study of women with a singleton, nonanomalous pregnancy delivering at a single academic medical center in the late preterm (340/7–366/7 weeks) or early term (370/7–386/7 weeks) period between 2010 and 2019. Women were categorized by diabetes status: no diabetes, type 1 (T1DM), type 2 (T2DM), or gestational diabetes (GDM). Multivariate logistic regression was used to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI) for risk of both mild and severe composite neonatal outcome with delivery in the late preterm or early term period using pregnancies without diabetes as the referent.Results A total of 8,072 pregnancies were included with T1DM, T2DM, and GDM complicating 1.8, 5.6, and 9.9% of pregnancies, respectively. Expected demographic differences were seen among groups including higher rates of non-Hispanic Black race, chronic hypertension, and higher body mass index in women with T2DM. The probability of severe composite adverse neonatal outcome was significantly increased in women with T1DM in the late preterm (aOR: 4.4; CI: 2.4–8.1) and early term (aOR: 1.6; CI: 1.1–2.3) periods, largely driven by the need for mechanical ventilation. The mild composite outcome was increased among all women with diabetes with early term delivery but highest in women with T1DM.Conclusion Pregnancies complicated by diabetes, particularly T1DM, have higher rates of neonatal adverse outcomes independent of gestational age at delivery, which is an important consideration when late preterm or early term delivery is planned.Key Points
Keywords: diabetes in pregnancy; neonatal outcomes; late preterm; early term